(untitled) (Bangladesh Journal of Public Administration, 2022)
Every profession has its professional stresses. In Bangladesh, the Veterinary profession is older. However, till now, itis not widespread due to several obstacles, and veterinary practitioners have to deal with these problems. There is a scarcity of veterinary professionals in Bangladesh, and the diagnostic tools are insufficient. The field condition of this sector is another problematic issue. A considerable number of quacks are providing services to the rural people of Bangladesh. The graduates are not able to do their private practice smoothly. So veterinary practitioners have to suffer more and more. This study represented the mental health condition and stressors of this profession. Google forms were provided for data collection through WhatsApp. This study used the Likert scale for the result and findings. In other countries, suicidal tendency is prevalent among veterinarians. However, till now, it is not typical case for vets to commit suicide in Bangladesh. However, the major problem in this study is professional burnout. Several other stressors led a veterinarian to face severe mental issues. In this study, it is seen that the socio Economic condition of a vet was not bad at all, But they had to face professional and social bullying. This study will help to reduce the stressors and provide a good and sound professional environment which will lead to mental problems and a free healthy, and wealthy life.